Research and publication ethics in developing countries - Sharma, Mohan Raj; Ghimire, Namita (Nepal Journal of Neuroscience, 2021)
The scientific validity of any project relies heavily on the ethically conducted and published research work. Conducting good quality research and publishing it in a scholarly, peer-reviewed journal is the ultimate dream of any researcher. However if not done without any research and publication ethics, the work will be counterproductive. Fortunately, there are several publications on ethics of research and publication guiding an early-stage researcher to follow the underlying principles. Research ethics include upholding the basic ethical principles of human research, namely, respect for persons, beneficence, and justice. Publication ethics involve not committing scientific misconduct, resolving authorship disputes, and avoiding simultaneous submission and duplicate publication. Repercussions of unethical research and publications are often unforgiving. Researchers in developing countries face unique challenges in this regard. However, at no cost should these principles be ignored. This will promote the development of a healthy research and publication culture, so desperately needed in these populations. Researchers, sponsors, ethical boards, publishers, and editors should work hand-in-hand to safeguard the research and publication integrity. In this review, issues surrounding research and publication ethics relevant to developing countries will be discussed.